Transformación de la familia en Colombia: mujer e infancia (1968-1984) - Jiménez Becerra, Absalón (Revista Científica, 2011)
The family as the primary institutional setting for the realization of children’s experience becomes the last decades of the 20th century, the development of Pharmacology and biotechnology, in which family plan- ning takes body product. In the Colombian area in the period to study are a series of initiatives designed to the protection of the family in 1968 was born the ICBF. The protection of the family is the protection of children, which ends up being subject to a number of practices and immanent to the child body speeches which seek to be indagados in this research.